â€œLebewohlâ€: A Musical Motif for Peace - Morrow, Ruth (European Scientific Journal, ESJ, 2017)
Music for human rights and social justice is very often a vehicle for words which then carry the lionâ€™s share of the interpersonal and musical communication. Music for solo piano which heightens our awareness of human rights and social justice issues exists without words, relying on extramusical representations and symbols to create a bridge between the music and our perception of it. The first movement of Ludwig van Beethovenâ€™s Piano Sonata in E-flat Major, Op. 81a, â€œDas Lebewohlâ€, will be discussed for its symbolism of grief and farewell over the Archduke Rudolphâ€™s forced exit from Vienna as Napoleonâ€™s troops advanced, as will the first movement of Sonata â€œ27 April 1945â€ of Karl Amadeus Hartmann, which uses Beethovenâ€™s motif from the first movement of Op. 81a as a primary reference in his musical outpouring of grief towards the imminent deaths of â€œpreventative detaineesâ€ from Dachau at the hands of the Nazis at the end of the Second World War. Through musicâ€™s connection to our nonverbal layers, these musical compositions can connect with our core selves, hold a mirror to our own belief systems and, if we are fortunate, bring us closer to peace.